Six hats for thinking about surrogacy and child protection (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article analyzes the main arguments on surrogacy and child protection using the method proposed by Edward De Bono, the “lateral thinking” theorist. This approach suggests a critique of the apodictic closure of the national legal thought to surrogacy, in order to make room for legal solutions that enhance the solidarity aspect of surrogacy itself. Furthermore, the government’s choices reflect a position that is hardly compatible with child protection. In the author’s opinion, in any case, remains a priority the need to legally guarantee the best interest of the child through immediate recognition of the parental responsibility of the couple resorting to surrogacy.
Keywords: Surrogacy; dignity; self-determination; best interests of the child; parental responsibility